A Quasi-Experimental Study on Efficacy of Quizizz in Enhancing Junior High School Students’ Grammar Performance - Devi Triani Agussalim; Yunitari Mustikawati; Ryan Rayhana Sofyan (International Journal of Language, Education, and Literature, 2025)
This quasi-experimental study investigated the efficacy of Quizizz as a digital game-based learning (DGBL) tool in enhancing students’ grammatical proficiency, with specific focus on their understanding and application of the simple present, present continuous tense, and simple past tense. Recognizing that grammar often presents significant challenges for English as Foreign Language (EFL) learners, this research aimed to explore a technology-driven approach to mitigate these difficulties and improve learning outcomes. Conducted during the 2024/2025 academic year at MTs DDI Baru, the study involved two comparable eight-grade groups: an experimental class (n=30) receiving grammar instruction facilitated by the Quizizz platform, and a control class (n=30) exposed to conventional, lecture-based teaching methodologies. Grammatical proficiency was quantitatively assessed through rigorously designed pre- and post-test, each comprising 30 multiple-choice questions specifically targeting the three aforementioned tenses. The findings showed a clear and significant improvement in grammar understanding among the students who used Quizizz. Their average test scores increased substantially, and many moved from a “Very Good” or “Excellent classification. The Mann-Whitney U test indicated a significant difference (U=287.000, p=0.016), supporting the hypothesis that Quizizz positively impacted grammar achievement. Furthermore, Cohen’s d of 0.63 demonstrated the educational meaningfulness of the intervention. In conclusion, the integration of Quizizz as a DGBL tool demonstrably improved students’ grammar proficiency. The inherent interactive nature, immediate feedback mechanisms, and engaging design elements of Quizizz facilitated a more effective and dynamic grasp of English tense structure and usage. This substantial enhancement suggests that Quizizz not only aids fundamental knowledge acquisition but also promote better retention of grammatical rules, transforming a traditionally challenging subject into an accessible and motivating learning experience. Therefore, the strategic adoption of interactive digital tools like Quizizz is highly recommended for English as a Foreign Language (EFL) grammar teaching, especially for junior high school students, to make language learning more effective and engaging.